Risk factors, repair techniques and short term subjective outcome of obstetrics anal sphincter injuries at Chris Hani Baragwanath academic hospital - Tshabalala, Salome Mokgohloe (My University, 2016)
Background Obstetric anal sphincter injuries (OASIS) complicates vaginal deliveries in 1-4% of patients globally. Risk factors include: Primiparity, increased birth weight > 4000g, assisted deliveries and precipitous labour amongst others. Aims and objectives To evaluate risk factors, describe repair methods at Chris Hani Baragwanath Academic Hospital (CHBAH) and assess outcomes post repair. Methods This was a prospective cohort study where 60 patients over the age of 18 with 3rd and 4th degree tears were recruited. Exclusion criteria: 1st, 2nd degree tear. Data was collected from medical files after repair. Women were interviewed telephonically at 6 and 12 weeks postpartum. Results The incidence of OASIS at CHBAH was 0.5%. Seventy-three percent of the study population were primigravids. End to end repair technique was popular amongst the surgeons (41.6%). Leakage of gas was the most common complaint of the patients reached at the follow up interview. Conclusion The low incidence of OASIS at CHBAH is similar to other studies. Primiparity was the leading risk factor in this study. Most of the patients were asymptomatic at follow up. Of those that were symptomatic, symptoms improved with time.
Faculty of Health sciences School of medicine Submitted in the partial fulfilment of the requirements for the degree of: Master of Medicine in Obstetrics and Gynaecology at Wits University Johannesburg, 2016